Jenis dan Kelimpahan Nyamuk di Resort Kembang Kuning, Taman Nasional Gunung Rinjani - Galuh Tresnani; Islamul Hadi; Yuliadi Zamroni (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to identify mosquito species as disease vectors and count their abundance in the Kembang Kuning Resort area, Mount Rinjani National Park. Larval samples were collected by traversing a 1.5 km trail. Samples were randomly collected from containers or water bodies containing larvae. The larval samples obtained from each 100 ml scoop were counted and identified by species. Some larval samples were reared to adulthood. Successfully hatched adult mosquitoes are identified by their species. Relative abundance is calculated from the number of larvae per scoop, and the container index (CI) value is calculated from the number of containers found positive for larvae. The research findings revealed 10 species belonging to family Culicidae and according to Rikhus Vektora (B2P2VRP, 2016), 9 of these species are vectors. The highest relative abundance values were found for the species Aedes albopictus (36.9%) and Culex quinquefasciatus (29.4%). The CI value for mosquitoes at Kembang Kuning Resort was 43.2%. The conclusion of this study is that Kembang Kuning Resort has 10 mosquito species, with the highest relative abundance for Aedes albopictus and Culex quinquefasciatus. A CI value greater than 5 indicates a relatively high risk of vector-borne disease transmission in this area.